2021
DOI: 10.19184/ejeba.v8i1.21144
|View full text |Cite
|
Sign up to set email alerts
|

Market Share Bank Syariah Terhadap Institusi Keuangan Syariah di Indonesia

Abstract: Sharia banking is a sharia financial institution that is considered to have contributed to the national economy. Judging from the value of the market share owned by Islamic banking, it is still relatively low compared to Malaysia. This study aims to determine the effect of Islamic capital market products and Islamic banking on the market share of Islamic banking assets in Indonesia. The Islamic capital market products used are in the form of Islamic stocks, corporate sukuk and Islamic mutual funds. Meanwhile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
2
0
4
Order By: Relevance
“…Assets serve as a key metric of progress within the banking sector, including Islamic banks, as they are used to gauge a bank's market share. Market share, in turn, determines a bank's competitive position relative to its peers (Adenan et al, 2021). Previous studies have consistently shown a significant increase in market share following the full conversion to a Sharia bank (Ribowo & Nurdin, 2022;Al Arif et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Assets serve as a key metric of progress within the banking sector, including Islamic banks, as they are used to gauge a bank's market share. Market share, in turn, determines a bank's competitive position relative to its peers (Adenan et al, 2021). Previous studies have consistently shown a significant increase in market share following the full conversion to a Sharia bank (Ribowo & Nurdin, 2022;Al Arif et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Perjanjian tersebut didasarkan pada hukum Islam, baik itu perjanjian yang dilakukan bank syariah dengan nasabah penghimpunan dana, maupun dalam penyaluran dana. Perjanjian atau akad yang terdapat di perbankan syariah harus tunduk pada syarat dan rukun akad tersebut (Ramadhan et al, 2022).…”
Section: Bank Syariahunclassified
“…This is a burden because the development of its market share does not match the ten successes of this industry. Market share is an indicator in determining the excellent value of the company in reaching the market against its competitors (Adenan et al, 2021). This symptom prompted the writer to conduct research entitled "Determinants of Market Share of Islamic Banking in Indonesia.…”
Section: Introductionmentioning
confidence: 99%